Oral health status and adverse pregnancy outcomes among pregnant women in Haryana, India: A prospective study - Puneet Singh Talwar; Ramandeep Singh Gambhir; Deepti Talwar; Ramandeep Kaur Sohi; Ashish Vashist; Vaibhav Munjal (Wolters Kluwer Medknow Publications, 2015)
Background: Women's oral health is affected by certain conditions such as pregnancy, puberty, menstrual cycle, menopause and nonphysiological conditions such as hormonal contraception and hormonal therapy. This study was conducted to assess the oral health status and treatment needs of pregnant women and to correlate periodontal health with adverse pregnancy outcomes like preterm birth (PTB) and low birth weight (LBW). Materials and Methods: A prospective study was undertaken at a Government Hospital in Haryana. Pregnant women who were in their third trimester of pregnancy and visited the hospital for routine ante-natal check-up constituted the final sample size (223). Dental caries and periodontal status were assessed using a WHO Proforma-1997. None of the subjects were in the habit of taking alcohol, chewing and smoking tobacco. The main outcome measures were gestational age and weight of the newborn. Data were analyzed using SPSS package version 13. Results: Decayed, missing and filled teeth index of the subjects was 2.87. Extraction was indicated in younger subjects when compared to the older ones. Bleeding was the main finding, which was present in 47.5% of the study subjects, followed by calculus. 63 more than 60% of subjects of subjects with 4-5 mm attachment loss belonged to 20-24 years age-group. There was a statistically significant association of probing depths and attachment loss with adverse pregnancy outcomes (P < 0.05) (PTB and LBW). Conclusion: There is a significant association between maternal periodontitis and pregnancy outcomes in the present study. It is recommended that suitable measures be undertaken by various health organizations to prevent periodontal problems among this particular group.